Efektifitas Pembelajaran Dengan Media Kartu Untuk Meningkatkan Kemampuan Pemahaman Matematis Siswa - Puji Lestari; Nina Sri Romdiani (Jurnal Gantang, 2018)
Learning methods with cards media have been widely used as one of the methods that are quite effective on enhancing students' learning ability. Two of them are Giving Question and Getting Answer (GQGA) and Question Student Have (QSH) methods. The aim of this research is to analyze the effectiveness of GQGA and QSH learning methods in improving students' mathematical understanding. The population of this research are 8th grade students of State Junior High School Garut district and the sample are 62 students. This research used a quasi-experimental with pretest-posttest control group design. The result shows that there is a difference enhancement of students 'mathematical understanding ability after being given GQGA and QSH methods, which means that the enhancement of mathematical understanding ability of students who get GQGA method better than the students who get QSH method. The size effect of two methods is in the medium category. This means that the use of card media in learning is quite effective on enhancing students' mathematical understanding. Keywords: mathematical understanding ability, GQGA method, QSH method.